2022
DOI: 10.1111/jocs.16558
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimal donor heart ischemic times in adult cardiac transplantation

Abstract: Objectives: Unsupervised statistical determination of optimal allograft ischemic time (IT) on heart transplant outcomes among ABO donor heart types. Methods:We identified 36,145 heart transplants (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) from the United Network for Organ Sharing database. Continuous and categorical variables were analyzed with parametric and nonparametric testing. Determination of IT cutoffs for survival analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…PGD which may result from myocardial stunning, leading to inadequate cardiac output which is beyond the capacity of the initial vasoconstrictive response to maintain cardiac afterload. The report of increase in PGD with longer ischemic time supports the second theory [57,58]. A third possibility is autonomic dyssynergia between the denervated cardioaccelerator beta 1 supply to the heart and the vasoconstrictive alpha supply to the vascular system.…”
Section: Post-operative Ecmo Use In Heart Transplantationsupporting
confidence: 56%
“…PGD which may result from myocardial stunning, leading to inadequate cardiac output which is beyond the capacity of the initial vasoconstrictive response to maintain cardiac afterload. The report of increase in PGD with longer ischemic time supports the second theory [57,58]. A third possibility is autonomic dyssynergia between the denervated cardioaccelerator beta 1 supply to the heart and the vasoconstrictive alpha supply to the vascular system.…”
Section: Post-operative Ecmo Use In Heart Transplantationsupporting
confidence: 56%
“…14 While an ischemic time of less than four hours is generally accepted as a threshold for optimal heart transplant outcomes, there is data to suggest that survival may be compromised at lower thresholds. 15 Likewise, our multivariate analysis demonstrated increased mortality due to longer ischemic time (Table 4).…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, in another study, it was observed that grafts from older patients exposed to an ischemic time of less than 120 min had better results compared to younger ones for the same time period [15], and another reported that ischemic time beyond 3 h is associated with increased mortality. Interestingly, there appeared to be greater vulnerability for grafts from blood group O donors compared to the others [16]. Finally, there is preliminary data on the use of special devices where ex vivo non-ischemic heart preservation is carried out to reduce the negative effects of the heart outside the body with very encouraging results [17].…”
Section: Ischemic Timementioning
confidence: 99%

Heart Transplantation

Chrysakis,
Magouliotis,
Spiliopoulos
et al. 2024
JCM